2010
DOI: 10.1007/s00572-009-0296-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of mercury in a soil–plant system as affected by inoculation with the arbuscular mycorrhizal fungus Glomus mosseae

Abstract: Effects of inoculation with the arbuscular mycorrhizal (AM) fungus Glomus mosseae on the behavior of Hg in soil-plant system were investigated using an artificially contaminated soil at the concentrations of 0, 1.0, 2.0, and 4.0 mg Hg kg −1 . Mercury accumulation was lower in mycorrhizal roots than in nonmycorrhizal roots when Hg was added at the rates of 2.0 and 4.0 mg kg −1 , while no obvious difference in shoot Hg concentration was found between mycorrhizal and nonmycorrhizal treatments. Mycorrhizal inocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
2
18
0
1
Order By: Relevance
“…We predicted that decreasing Hg content in roots is one of Hg tolerance mechanisms in mycorrhizal symbiosis. This result was in line with Yu et al (2010), AMF Glomus mosseae decreased significantly Hg concentration in maize roots when Hg -1 was applied at the rates of 2.0 dan 4.0 mg kg . All interactions of Hg with soil/growth media, roots, and AMF influence its uptake by plants, but this presume need to be investigated in further research.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We predicted that decreasing Hg content in roots is one of Hg tolerance mechanisms in mycorrhizal symbiosis. This result was in line with Yu et al (2010), AMF Glomus mosseae decreased significantly Hg concentration in maize roots when Hg -1 was applied at the rates of 2.0 dan 4.0 mg kg . All interactions of Hg with soil/growth media, roots, and AMF influence its uptake by plants, but this presume need to be investigated in further research.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is in line with Rabie (2005) who reported that sensitivity of AM symbionts to heavy metal polluted soil expressed as a reduction in root colonization. In contrast, addition of Hg in soil did not significantly influence maize root colonization rate (Yu et al 2010). Another interesting result showed at Table 7, the presence of AMF could increase the metal tolerance index of E. cyclocarpum seedlings compared with nonmycorrhizal seedlings when they treated with 750 µM Hg.…”
Section: Rootsmentioning
confidence: 89%
See 1 more Smart Citation
“…Results of statistical analysis, however, showed that AM fungi inoculation did not significantly affect the accumulation of mercury. This might indicate a loss of Hg which can be attributed to Hg volatilization as a result of AM fungi influence (Yu et al, 2010). All treatments posed TF values of more than 1, i.e.…”
Section: Mercury Accumulation By P Conjugatum Ckyllingia and Lcrmentioning
confidence: 99%
“…It is thought that the bioavailability of mercury in the rooting zones of the three plant species declined into a form that was less soluble as absorbed by organic compounds released by plant roots, or absorb the metal into the root surface, and then accumulated the metal in the plant tissues (Berti and Cunningham, 2000;Wong, 2003). Outside the roots, the hyphae and root surface can absorb Hg so that Hg translocation into roots can be inhibited, and inside the roots, it changes cell wall components of plant, hence possibly enhancing the sequestration of Hg (Yu et al, 2010).…”
Section: Mercury Accumulation By P Conjugatum Ckyllingia and Lcrmentioning
confidence: 99%